Tranexamic acid in arthroscopic surgery: efficacy, safety, and clinical considerations - Wang, Wei; Tian, Qi ru; Li, Sheng (Frontiers in Surgery, 2025)
This study reviews the applications and effects of tranexamic acid in arthroscopic surgery. Bleeding during arthroscopic surgery is an important factor affecting surgical outcomes and postoperative recovery. Tranexamic acid is an anti fibrinolytic drug that can effectively inhibit fibrin degradation and may be helpful in reducing surgical bleeding and improving surgical field clarity. In this review, the pharmacological mechanism of tranexamic acid is first introduced, including its effect on the fibrinolytic system and its specific mechanism of action to reduce bleeding. Subsequently, the review describes the application of tranexamic acid in arthroscopic surgery, analyzes the safety of tranexamic acid in arthroscopic surgery, and related factors affecting the effectiveness of tranexamic in arthroscopic surgery. In addition, this review highlights future research directions regarding tranexamic acid in arthroscopic surgery. A comprehensive analysis of existing literature indicates that tranexamic acid has an impact on blood loss, pain, surgical time, surgical field clarity, and postoperative function during arthroscopic surgery. Therefore, the application of tranexamic acid in arthroscopic surgery has high clinical value and significance.